A magyar királyság határkiigazításának költségei 1890-1918 között: COSTS OF THE BORDER ADJUSTMENT OF THE KINGDOM OF HUNGARY BETWEEN 1890-1918 - Suba, János (Közép-Európai Közlemények, 2020)
Az államhatárok megvonása egyben a terület szuverenitását is kijelöli, hiszen az államhatárok az államok kizárólagos hatalma (szuverenitása) alá eső területeket választanak el egymástól. A határok pontos megvonása ezért mind az állam belső élete, mind az államközi kapcsolatok szempontjából elengedhetetlen. Nem jogi, hanem politikai kérdés, hogy egy tényleges esetben hol vonják meg a határt. Az államhatár lényege, hogy nemzetközi jellegű választóvonal. A jogi feltételeknél első helyen az országgyűlés által hozott törvénycikkek állnak.] Ezek lezárták a két ország között politikai síkon lezajlott tárgyalásokat, az elért eredményeket rögzítik, másfelől ez a további munkák kiindulási alapja, mert meghatározzák a műszaki munkálatok menetét és a továbblépés lehetőségét. A határviták, és azok megoldása mindig végig kísérték a magyar törvényalkotást. The most important condition for solving the border issue is to create proper financial circumstances as it indicates how seriously the task is taken. This study reviews the financial conditions of the border designation. These amounts primarily apply to the technical tasks: the costs of layout, boundary markers and mapping.In the given period it could take place as part of the yearly budget approved by the law, in a general term, like ’for national border adjustment’ or under a particular name. It usually turned out within the procedure that the money was not enough, as always, therefore additional loans were necessary later approved by the Council of Ministers. It could be carried out using the budget of one of the Ministries. The study reviews the financial conditions of the border designation based on these perspectives. One of the most important tasks of the parliament was to approve the yearly Budget Act. The border designation as an item in the budget first appeared in paragraph IV, 1890 in the column ’costs of Ministry of Interior’. The last itemized denomination was the paragraph XXII, 1916, in which the cost of border designation appeared at the Ministry of Interior among the regular outcomes, while it belonged to the transitional outcomes at the Prime Minister’s Office